Value of travel time savings and willingness to pay for regional aviation. (February 2017) - Merkert, Rico; Beck, Matthew
Highlights: We show first empirical evidence on the willingness to pay for regional air services. Mixed logit choice models are applied to the context of travel from city to regional Australia. Car is the most preferred option for regional travel followed by air. Value of time travel savings of 126 per hour for plane journey useful for competitive pricing. Aviation essential to regions but also of high value to residents/businesses in cities. Abstract: Despite their immense importance to regional and remote communities, regional air services are often commercially not viable and need public support. That support, and hence the existence of such lifeline services, is often questioned by stakeholders and policy makers. While the value of these services is high to the passengers and businesses that are located in regional, rural and remote areas, there is only anecdotal and no robust evidence available on the value of such services to people who live in metropolitan areas. This paper applies mixed logit choice models to a large sample of the Sydney metropolitan area to establish, for a first time, empirical evidence on the value of travel time savings (VTTS) and the willingness to pay for regional air services. While car is the most preferred option for regional travel (chosen most), we find a median willingness to pay of 99 per hour for leisure travel via plane and 153 per hour for business travel. Additional analysis on VTTS for different modes across leisure versus business travel is also conducted, providing for a more detailed understanding of each traveller type and willingness to pay differences between the various groups. The findings are of substantial value to regional airlines, airports, regulators, funding bodies and policy makers as they show that regional aviation is not only invaluable to the regions but also of high value to residents and business travellers residing in metropolitan areas.